Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton University Press, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Section: x, 286 pages ; 24 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Beyond Binary: Genderqueer as Critical Gender Kind - Dembroff, Robin (Philosophers' Imprint, 2020)
We want to know what gender is. But metaphysical approaches to this question solely have focused on the binary gender kinds men and women. By overlooking those who identify outside of the binary–the group I call ‘genderqueer’–we are left without tools for understanding these new and quickly growing gender identifications. This metaphysical gap in turn creates a conceptual lacuna that contributes to systematic misunderstanding of genderqueer persons. In this paper, I argue that to better understand genderqueer identities, we must recognize a new type of gender kind: critical gender kinds, or kinds whose members collectively destabilize one or more pieces of dominant gender ideology. After developing a model of critical gender kinds, I suggest that genderqueer is best modeled as a critical gender kind that destabilizes the ‘binary axis’, or the piece of dominant gender ideology that says that the only possible genders are the binary, discrete, exclusive, and exhaustive kinds men and women.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sofia; systèmes d'oppressions; thématiques; états-unis

Conceptualiser l’oppression épistémique - Dotson, Kristie (Recherches féministes, 2018)
L’oppression épistémique désigne une exclusion épistémique persistante qui empêche ou limite la contribution d’une personne à la production des savoirs. On hésite à parler d’« oppression épistémique », et cela tient peut-être à la prémisse voulant que les formes épistémiques de l’oppression se ramènent en général à ses formes politiques et sociales. L’auteure convient que de nombreuses formes d’exclusion qui compromettent la capacité d’une personne à contribuer à la production des savoirs peuvent être ramenées à des formes d’oppression politique et sociale, mais il existe néanmoins des formes distinctes et irréductibles d’oppression épistémique. Elle soutient ainsi que la différence fondamentale entre les formes réductibles et irréductibles d’oppression épistémique réside dans le type de résistance à laquelle on fait face dans chaque cas, c’est-à-dire le pouvoir épistémique ou les caractéristiques des systèmes épistémologiques. La distinction entre les formes réductibles et irréductibles d’oppression épistémique permet de mieux comprendre les enjeux que soulève l’emploi de cette expression et la pertinence d’y recourir.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; invisibilisation; phi4336; philosophie; premier cycle; production des savoirs; pédagogie; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie

Considérations éthiques sur le consentement comme noyau de la sexualité - Viola, F.J.J. (Sexologies, 2015)
La notion de consentement est plus souvent associée aux plaintes pour agression sexuelle qu’aux études et thérapies sexologiques où l’objectif d’une « vie sexuelle satisfaisante » relègue l’idée de contrainte à l’arrière-plan.Dans cet article, nous voulons montrer que, sous l’angle du questionnement sexologique, la notion de consentement recouvre plus que l’accord entre deux personnes quant à un acte ou une relation univoque. Dans la thérapie sexologique, il occupe même une place centrale, tant comme question éthique (qui positionne le thérapeute) que comme contenu de la consultation (comme dessous des plaintes formulées).Une analyse de la littérature médicale fournit des éclairages à l’appui du concept clinique de « consentement pluridimensionnel ». Trois exemples extraits de notre clinique illustrent sa pertinence.Nous suggérons que trois « constantes » soient prises en compte explicitement dans la clinique : la conception du monde, déterminant pour le consultant sa perception d’une « sexualité normale » ; les rapports de pouvoir, s’établissant au sein de tout rapprochement de personnes et la négociation, inévitable perspective pour qu’une quelconque association puisse tenir.L’accès à « une vie sexuelle satisfaisante » passe pour le consultant par l’identification de ce à quoi au juste il a consenti dans le contexte qui fonde sa plainte. Le sexologue l’y aidera par l’attention accordée d’entrée de jeu à ces trois constantes qui forment la charpente du consentement.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; canada; consentement; corps; cours; discipline; phi2030; philosophie; premier cycle; périodes historiques; rapports de pouvoir; régions géographiques; sciences humaines; sexualité; thématiques

Young, Black and male : Exploring the intersections of racial and gender identity in an all-Black male high school - Rogers, Leoandra Onnie (New York University, 2012)
From popular culture to academia, there is national panic about the dismal life trajectories of Black males. This "Black male crisis" has contributed to emergent all-Black, all-male schools. Racial identity is commonly used to explain underperformance among Blacks, yet within-group gender disparity signifies the importance of gender relative to race. Minimal research exists on Black males' gender identities, and less on the intersections of gender and race. This longitudinal dissertation used quantitative and qualitative data to examine the development and intersections of racial and gender identity among Black adolescent males transitioning from co-educational grammar schools and entering the ninth grade at an all-Black, all-male high school. Findings are presented in two empirical papers. Paper 1 examined survey data collected from Black males (N = 183) to explain how boys' racial and gender identities were interrelated, changed over time, and influenced their psychological and academic adjustment. Results from the growth curve analysis revealed that boys' racial and gender identities were interrelated with each other and that higher levels of identity attachment were associated with better psychological and academic adjustment. Moreover, the strength of the relationship between gender identity and psychological adjustment increased over time, indicating that gender identity became increasingly important for boys' wellbeing. Paper 2 analyzed interview data with a subsample of Black males (n = 21) to examine how they resisted and accommodated racial and gender stereotypes. Results from the qualitative analysis revealed that boys were aware of the ways that racial and gender stereotypes overlap, but they responded to these stereotypes in different ways. Although some boys accommodated to both racial and gender stereotypes and others resisted these stereotypes, the majority of the boys responded by accommodating to gender stereotypes and resisting racial stereotypes. That is, they tended to perpetuate cultural stereotypes that require males to be the leader, emotionally stoic, and not to be feminine (i.e., gay) while challenging beliefs about the intellectual inferiority and incompetence of Black people. Findings are interpreted within the macro-context of cultural stereotypes and the micro-context of an all-Black male school. Implications for the study of identity, Black males, and single-sex education are discussed.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; adolescence; amériques; approches et analyses; chicago; discipline; genre; hommes* noirs; identité raciale; intersectionnalité; mémoires/thèses; philosophie; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes; étude longitudinale; étude qualitative; étude quantitative

Gabriel Girard – Interview Elsa Dorlin : Le Queer est un matérialisme - Girard, Gabriel (Syllepse, 2007)
Interview d'Elsa Dorlin pour l'ouvrage "Femmes, genre, féminismes".
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; philosophie; philosophie politique; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; états-unis